Níveis de proteína digestível e energia digestível em dietas para tilápias-do-nilo formuladas com base no conceito de proteína ideal - Goncalves, Giovani Sampaio; Pezzato, Luiz Edivaldo; Barros, Margarida Maria; Hisano, Hamilton; Santa Rosa, Maria Julia [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2009)
This study was carried out to determine the best digestible energy and digestible protein ratio in feeds for Nile tilapia (Oreochromis niloticus) juveniles 30.0 +/- 4.21 g) based on digestible amino acids and the ideal protein concept). Twelve rations were formulated with protein levels 22.0; 26.0; 30.0 and 34.0% of digestible protein and levels 3,000, 3,300 and 3,600 kcal/kg digestible energy. The digestible energy/digestible protein ratio was between 8.94 and 15.19 kcal/g. Three hundred and twenty four tilapias were randomly distributed in thirty six 250 L circular tanks at a density of 9 fish/tank, a total of 12 treatments with three replications. After 60 days, there was no significant difference in weight gain, daily weight gain and feed conversion ratio among the studied treatments. A linear increase was observed in fillet yield with increasing digestible protein. With respect to feed cost/kg weight gain, the treatment with 30.0% DP and 3,000 kcal/kg DE presented low cost and better cost effectiveness index. Therefore, it was concluded that digestible energy did not influence the productive performance parameters and that effective feeds can be formulated with DP levels lower than 34% when feeding juvenile tilapias. The ration should be formulated based on the concept of ideal protein.

Este estudo foi realizado para determinar a melhor relação energia digestível/proteína digestível em rações formuladas com base em aminoácidos digestíveis e aplicando-se do conceito de proteína ideal para juvenis (30,0 ± 4,21 g) de tilápia-do-nilo (Oreochromis niloticus). Foram formuladas 12 rações com 22,0; 26,0; 30,0 ou 34,0% de proteína digestível e 3.000, 3.300 ou 3.600 kcal/kg de energia digestível, com relação proteína digestível/energia digestível variando entre 8,94 e 15,19 kcal/g. Foram utilizadas 324 tilápias, distribuídas aleatoriamente em 36 aquários circulares com volume de 250 litros, em densidade de 9 peixes/aquário, perfazendo 12 tratamentos e 3 repetições. Ao final de 60 dias, não foi observada diferença no ganho de peso, no ganho de peso diário e na conversão alimentar entre as relações energia/proteína avaliadas. Entretanto, observou-se aumento linear do rendimento de filé com o aumento dos níveis de proteína digestível. O custo de ração por kg de ganho de peso foi menor nos peixes alimentados com a ração com 30,0% PD e 3.000 kcal/kg ED, os quais apresentaram também melhor índice de eficiência econômica. A energia digestível não influenciou o desempenho produtivo, portanto, é possível a utilização de níveis inferiores a 34,0% proteína digestível em rações com base no conceito de proteína ideal para juvenis de tilápia.
Level of digestible protein and digestible energy in diets for Nile tilapia formulated based on the concept of ideal protein
Keywords: amino acids; nutrition; Oreochromis niloticus; protein requirement